Preparation And Characterization Of Epoxidized Soybean Oil Based Thermoset, Blends And Nanocomposites - Tan , Seah Guan (2013)

(untitled)
Epoxidized soybean oil (ESO) was thermally-cured with methylhexahydropthalic anhydride (MHHPA) curing agent in the presence of two different types of catalysts, i.e., 2-ethyl-4-methylimidazole (EMI) and tetraethylammonium bromide (TEAB). The cure kinetics of ESO/MHHPA was studied using the Fourier Transform Infrared Spectroscopy. The cure temperatures and catalyst contents showed significant effects on the kinetic rate constants, overall reaction orders and activation energies of ESO/ MHHPA systems. The critical conversion was found to be 0.6‒0.8. Cure kinetics of ESO could be well-described by adding the diffusion factor into Kamal’s model. The thermal properties of ESO thermosets were studied by dynamic mechanical analyzer, thermogravimetry analyser, differential scanning calorimetry and gel content measurement. The glass transition temperature (Tg), storage modulus (E’), gel content, crosslink density, degree of conversion and thermal stability increased with increasing EMI and TEAB content. The fracture toughness of ESO thermosets was studied using linear elastic fracture mechanics and essential work of fracture. The fracture toughness (KIC) and the specific essential work of fracture (we) of the ESO thermosets increased with increasing the EMI and TEAB content. A reduction in KIC and we of the ESO thermosets were found if the TEAB content exceeded 0.5 phr. The water absorption test for ESO thermosets was conducted at room temperature for 3 months. The maximum water uptake and the diffusion coefficient of the ESO decreased with increasing catalyst content. Two strategies, i.e., blending with the diglycidyl ether of bisphenol-A (DGEBA) and reinforcing with organomontmorillonite clay (OMMT), were used to improve the mechanical and thermal properties of ESO. A miscible blend with an interpenetrating polymer network (IPN) structure was obtained by adding DGEBA into ESO. The IPN structure was evidenced by transmission electron microscopy and atomic force microscopy. The synergistic enhancement in modulus, tensile strength, Tg, crosslink density and thermal stability of the ESO/DGEBA blends could be associated to the possible interpenetrating network of the blends. These mechanical and thermal properties of ESO were also improved by the addition of OMMT. Such improvements arose from the co-catalytic effect of octadecyl trimethyl ammonium (intercalant of OMMT) to facilitate the cure reaction of ESO, that in turn promoted the crosslink formation. The biodegradability of ESO in the compost soil was also studied. ESO thermosets were biodegraded by the soil microbes under the compost soil environments. The extent of biodegradation of ESO was determined from weight change measurement. It was found that the weight loss of ESO was governed by the crosslink density and soilburied exposure time. From the 16S rDNA sequencing approach, it was determined that Comamonas sp., Bacillus sp., Streptomyces sp. and Acinetobacter sp. are the possible soil microbes to degrade the ESO